2014
DOI: 10.1186/1471-2393-14-338
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of high risk pregnancy contributing to perinatal morbidity and mortality from a birth population-based regional survey in 2010 in China

Abstract: BackgroundNeonatal mortality reduction in China over past two decades was reported from nationwide sampling surveys, however, how high risk pregnancy affected neonatal outcome is unknown. The objective of this study was to explore relations of pregnancy complications and neonatal outcomes from a regional birth population.MethodsIn a prospective, cross-sectional survey of complete birth population-based data file from 151 level I-III hospitals in Huai’an region in 2010, pregnancy complications were analyzed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 25 publications
0
21
0
3
Order By: Relevance
“…Approximately 10% of pregnancies have complications from a birth population-based regional survey of estimation of high-risk pregnancy contributing to perinatal morbidity and mortality in 2010 in China. [15] Moreover, multivariate logistic regression of this study revealed that pregnancy complications as well as multiple births, birth defects, and mothers’ biological and social status were significantly associated with the neonatal outcome, indirectly reflecting the influence of pregnancy complications and other perinatal risks. Home birth with lack of sterilization, warming, resuscitation and other resources is another high-risk factor related to neonate death.…”
Section: Discussionmentioning
confidence: 83%
“…Approximately 10% of pregnancies have complications from a birth population-based regional survey of estimation of high-risk pregnancy contributing to perinatal morbidity and mortality in 2010 in China. [15] Moreover, multivariate logistic regression of this study revealed that pregnancy complications as well as multiple births, birth defects, and mothers’ biological and social status were significantly associated with the neonatal outcome, indirectly reflecting the influence of pregnancy complications and other perinatal risks. Home birth with lack of sterilization, warming, resuscitation and other resources is another high-risk factor related to neonate death.…”
Section: Discussionmentioning
confidence: 83%
“…A study conducted in Latin America and the Caribbean with women in prenatal care and a number of consultations of less than six due to pregnancy complications and interruption of pregnancy found higher mortality rates and greater frequency of NM cases and fetal and neonatal deaths (15) . In other studies in China and Brazil, it has been shown that complications in pregnancy result in higher rates of fetal and neonatal death, prematurity and death at birth (5,20) . In this study, the history of previous stillbirths was a risk factor for AFNO, with a statistically significant result.…”
Section: Discussionmentioning
confidence: 95%
“…Although studies on near miss (NM) are frequent in recent years, there are few studies on perinatal complications among these patients, as well as studies that relate MNM to early fetal and neonatal death. Recent research in Brazil and China on such a relation shows that mothers who have had obstetric complications have an increased risk for fetal and neonatal death as well as for neonatal prematurity and asphyxia (3,5) . In this context, fetal and neonatal adverse outcome (FNAO) among NM patients has yet to be explored.…”
mentioning
confidence: 99%
“…3 Clear trend was observed in a study in China between higher pregnancy complications and fetal deaths (including stillbirth) and early neonatal death. 8 Apgar score had better scores in low risk group. 58 cases were observed in with score more than 7, and 14 cases with score less than 4.…”
mentioning
confidence: 90%
“…In a study in China, average length of hospital stay in high risk group was 8.5±6.3 days, and, 99.2% of babies received antibiotics. 8 It was further observed that, this trend should have been more prominent and relevant in the emerging regions, requiring advanced perinatal care system emphasizing on routine…”
mentioning
confidence: 99%